Инновационное совершенствование системы спортивной подготовки в профессиональном баскетболе - Белькович, В.Н.; Трубицкая, Л.А.; Процюк, О.А. (My University, 2013)
This article discusses three ways management research in the university, depending on the characteristics of the individual lstudent. Just consider the use of various types of educational research, design and research activities as a form of research skills. The paper reveals the need to improve the technology of preparation of professional basketball players. Such technology should be innovative in nature and cover all areas of professional gaming activities. This work is devoted to a study of the latest technologies of training basketball players.